Rethinking policy piloting : insights from Indian agriculture - Nair, Sreeja (Cambridge : Cambridge University Press, 2021)
Piloting is an important form of policy experimentation and a promising tool for policymakers to innovate, formulate and test alternative policy designs for the future. While this is recognized in theory, there are several challenges in realizing a pilot's potential to do so in practice. Addressing these challenges ask for a deeper understanding of the design of policy pilots and their outcomes in terms of how they mainstream into routine policymaking. Looking back at selected national piloting initiatives in Indian agriculture over a period of twenty-five years, this book draws insights for policy theory and practice. Design features of pilots that are found to influence their scaling-up and translation into formal policies (or not) are distilled from literature and compared across the selected cases. Theoretical insights from the book can be extended and adapted to agricultural policymaking in other Asian countries as well as to policy formulation in other sectors.
Rethinking Policy Pilots in the 21st Century -- The Context of Indian Agriculture for Piloting -- A Landscape of Agriculture Policy Pilots -- A Qualitative Comparative Analysis of Policy Pilots -- From Piloting to Policy: Lessons and the Path Ahead.
Title from publisher's bibliographic system (viewed on 06 Aug 2021).
Keywords: Agriculture and state -- India; Agricultural administration -- India